Experiencing Sampling Research from Its Beginnings into the Future. (1st October 2019) - Larson, Reed W.
Abstract : Early experience sampling research sought to map the ecology of adolescents' lives. Its contributions include discovery of similar patterns in psychological states across diverse samples: positive emotions with friends, more negative states alone, high challenge but low motivation during schoolwork, and wider variability in teens' than adults' emotions, including more frequent extreme positive states. Recent ambulatory assessment research has expanded this mission and methods in valuable ways. Yet it still demands problem‐solving (e.g., engaging participants, formulating analyses that represent teens' complex lives). A promising innovation is use of micro‐longitudinal analyses to examine sequential processes (e.g., linkages between stress–coping–emotions; relationship episodes). Qualitative data can add "zones" for development of empirically‐based theory about daily processes, such as adolescents' meaning‐making and learning self‐regulation.